Emerging Adulthood and Nonlinear Dynamic Systems Theory. Issue 1 (31st March 2017) - Knight, Rona
ABSTRACT: The papers in this section on emerging adulthood exemplify the continuous interaction of the cultural surround, biology, and psychology that support a nonlinear dynamic system of development. People in their twenties move through this developmental period in individualized ways, and their ability to successfully traverse these years to adulthood can be helped or hindered by the complex interplay of their individual psychology, environment, and culture.